Non-farm employment trends and policy in rural areas of Samarkand region (Uzbekistan) - Shavkat Hasanov; Golib Sanaev (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
Nonfarm employment plays an important role in absorbing unemployment in rural areas of developing countries. The agricultural transition in Uzbekistan followed by structural transformations in the economy changed the rural economy. Although farm restructuring and farm optimization policies led to agricultural growth, they had a negative impact on rural employment. The government of Uzbekistan promoted many policies to create jobs within the country. A presidential decree launched the State Program on Rural Development and Well-being in 2009, which played a crucial role in developing the economic and social infrastructure of rural areas. Small business and private entrepreneurship were given priority to absorb the rising unemployment, especially in rural areas. Against this background, the paper studies non-farm employment trends in rural areas of Samarkand region. In particular, we explore the main drivers of non-farm business development and its impact on rural employment in the Samarkand region. The main employment trends in rural areas of Samarkand region are described using statistical data. We also explore migration trends in Uzbekistan and Samarkand regions. A survey was conducted with 34 mahallas' (community) chairpersons and representatives to better analyze the intersectoral and international migration of the agricultural workforce. Although remittances are crucial in poverty alleviation of Central Asian countries, including Uzbekistan, the economic crisis in 2008-2009 in Russia cast a shadow on the further prospects of migration. We show how the development of non-agricultural business in the Samarkand region increased the incomes of the rural population. The agro-processing sector plays a vital role in creating clusters based on the agro-industrial complex, which in turn will create more opportunities for employment in rural areas of the country.
urn:nbn:de:gbv:3:2-100755
Keywords: P41; J60; J68; 330; Employment; the Rural Nonfarm Economy (RNFE); Non-Agricultural Business; Rural Area; Samarkand Region